Multifaceted Telmisartan: Candidate for new therapeutic approaches - Prince Sanjeev Yoganand; Raison Chacko; Rajeshwar Kant Chandra Mishra; RLV Phani Kumar; Saikat Kundu (Medico Research Chronicles)
Telmisartan is an Angiotensin II type 1 (AT1) receptor blockers (ARBs), that is highly selective for the AT1 receptor and has a long duration of action because of its long terminal elimination half-life1. Telmisartan is considered to be the most potent member of the sartan group because, in addition to AT1R blockade, it strongly activates the antiinflammatory nuclear receptor, peroxisome proliferator-activated receptor γ (PPAR γ)